Identifying potential barriers to community participation and use of telecentres: A Survey-based Study - Jeremy Brown (Information Research: An International Electronic Journal)
Introduction. Telecentres have been set up in most developing countries to bring digital access to as many people as possible. The main issues associated with these telecentres' sustainability include cultural, technical, financial, social, political, and programmatic issues that directly affect these centres' sustainability. Therefore, the present study adopts a community-centred approach by discussing users' views and perceptions and non-users from the local community.